Designing an E-Business Model in Iranian Sports Tourism with Emphasis on Organizational Factors - Abolfazl Farahani; Lachin Noorollahi; Alimohammad Safania; Reza Nikbakhsh (Research in Sport Management and Marketing)
Purpose: The aim of this study was to designing an e-business model in Iranian sports tourism ‎with ‎emphasis on organizational factors ‎Methods:‎‏ ‏the research method was derived from grounded theory for explaining and analyzing ‎findings ‎‎from exploratory interviews. The study population was the Professors, top startup ‎managers in ‎the ‎field of tourism and managers of Iran sports tourism association, touring & ‎automobile club ‎of the Iran, IFTGA(Iran Federation of Tourist Guide Associations), and ‎electronic business ‎expert’s ministry of cultural heritage, handicrafts ‎and tourism. The sampling ‎method was a ‎combination ‎of purposeful sampling and snowball. ‎The ‎research tool included an ‎open source ‎‎interview. In the data analysis phase, the ‎content ‎analysis and counts of the themes ‎‎were employed ‎in open, axial and selective ‎coding stages‎. ‎ ‎‏Results: The results of the data obtained from the interviews during the ‎open, pivotal and ‎selective ‎codification process led to the creation of the data driven theory in ‎the field of e-‎business model in ‎Iranian sports tourism with emphasis on organizational factors ‎‏.‏‎ ‎According ‎to the study, e-business ‎Sports tourism is a multi-sectoral structure that is affected by ‎a set of ‎underlying factors, ‎intervening conditions, causal conditions, strategies and ‎consequences.‎Conclusion: In general in the world at present, e-business tourism sports will not succeed if ‎they are ‎‎not equipped ‎with these organizational skills‎. Therefore, the integration of ‎organizational factors ‎in ‎the field of sports tourism can help in the development of e-business ‎in sports tourism. ‎